Práticas de preservação da memória social nas instituições-memória da cidade de Belém (Pará) - Martins, Eliane Epifane (2017)
This research aims to characterize the memory institutions of the city of Belém/PA and conservation practices of cultural heritage, understanding of the historical point of view the functions and objectives of these institutions, in addition to presenting preservation practices and strategies established for the preservation of their cultural heritage. The theoretical contribution was based on authors such as: Halbwachs (2003), Nora (1993), Gondar (2005), Assmann (2011), Dodebei (1997) Sant ' Anna (2009), among others. The methodology here employed is supported by fieldwork, documental research, and documental analysis, which is in its turn based on the work “The historical research: theory and method", by Júlio Aróstegui (2006). As result, eight memory institutions was identified: Public Archive of the State of Pará, Museum of the State of Pará, Art Museum of Bethlehem, Museum of the Candle, Museum of Sacred Art, Museum of the Fort of the manger, Museum of Gems of Pará and the Memory Center of Amazonia. Finally, cultural heritage preservation strategies and practices are presented, in addition to how those memory institutions spend their budgets.